2021
DOI: 10.1080/15384101.2021.1890951
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chondroitin polymerizing factor (CHPF) as tumor promotor in cholangiocarcinoma through regulating cell proliferation, cell apoptosis and cell migration

Abstract: Background: Cholangiocarcinoma (CCA) is a variety of biliary epithelial tumors involving intrahepatic, perihilar and distal bile duct. It is the most common malignant bile duct tumor in the liver and the second most common primary liver cancer, whose molecular mechanism not fully understood. Speci cally, the relationship between CCA and chondroitin polymerizing factor (CHPF) is still not clear. Methods: In this study, detection of clinical specimens was performed to preliminarily study the role of CHPF in chol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The recent studies found CHPF is significantly up‐regulated in multi‐malignancies, its aberrant expression is related with a poor biological behaviors and predicts a poor prognosis. The high‐expression of CHPF promotes tumor progression and mediates therapeutic resistance (Fan et al 2017; Hou et al 2019b, a; Hou et al 2019b, a; Sun et al 2020; Xu et al 2020; Duan et al 2021; Lin et al 2021). In this study, we found that CHPF is significantly increased in human BRCA tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent studies found CHPF is significantly up‐regulated in multi‐malignancies, its aberrant expression is related with a poor biological behaviors and predicts a poor prognosis. The high‐expression of CHPF promotes tumor progression and mediates therapeutic resistance (Fan et al 2017; Hou et al 2019b, a; Hou et al 2019b, a; Sun et al 2020; Xu et al 2020; Duan et al 2021; Lin et al 2021). In this study, we found that CHPF is significantly increased in human BRCA tissues (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The recent studies reported that CHPF aberrant expression promotes multiple tumor progression and mediates the therapeutic resistance. It is significantly up‐regulated in human melanoma (Sun et al 2020), glioma (Fan et al 2017), gastric cancer (Lin et al 2021), hepatocellular carcinoma (HCC) (Xu et al 2020), cholangiocarcinoma (CCA) (Duan et al 2021), non‐small‐cell lung cancer (NSCLC) (Hou et al 2019b, a; Hou et al 2019b, a) and breast cancer (BRCA) tissues (Li et al 2021a, b, c; Liao et al 2021), the high‐expression of CHPF is closely related with the advanced stage and predicts a poor prognosis. CHPF knockdown can inhibit the proliferation, cell cycle evolution, epithelial‐mesenchymal transition (EMT), migration and invasion in these malignancies.…”
Section: Introductionmentioning
confidence: 99%
“…CCA is the closest to FLC in terms of CSGALNACT and VCAN upregulation. Intriguingly, CHPF has been reported recently to promote CCA cell growth and invasive potential (56). In addition, CHSY has been reported to suppress apoptosis in colorectal cancer (57) and promote migration in HCC (58).…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiocarcinoma (CCA) is the closest to FLC in terms of CSGALNACT1 and VCAN upregulation. Intriguingly, chondroitin polymerizing factor ( CHPF ) has been reported recently to promote CCA cell growth and invasive potential (44) . Additionally, chondroitin synthase 1 ( CHSY1 ) has been reported to suppress apoptosis in colorectal cancer (45) and promote migration in hepatocellular carcinoma (HCC) (46) .…”
Section: Discussionmentioning
confidence: 99%